SARS-CoV-2 infection in kidney transplant recipients: clinical impact and outcomes - a single center experience - Santos,Afonso (2021)
ABSTRACT Introduction: Kidney transplant recipients are a subgroup of patients at higher risk of critical forms of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection and poor outcomes due to immunosuppression treatment. Herein, we present data from a single center cohort of kidney transplant recipients with SARS-CoV-2 infection. Methods: In a prospective study, baseline characteristics, clinical features, antiviral and immunosuppression management were compared between outpatients and hospitalized patients, during a one-year period. Results: Seventy-seven kidney transplant recipients were analyzed, including outpatients and hospitalized patients, with a median age of 57.7 (IQR 49.7-64.9) years. Twenty-eight (36.4%) were managed as outpatients, while 49 (63.6%) patients required hospital admission. Among hospitalized patients, 18.4% were admitted in ICU, 49% had AKI, and 20.4% died. Immunosuppression adjustments were performed in 95.9% of hospitalized patients, with dose of anti-metabolites adjusted in 83.7%, mTOR inhibitors in 14.3%, calcineurin inhibitors in 12.2%, and corticosteroid therapy in 81.6%. Conclusion: Among hospitalized patients, immunosuppression management included reduction or withdrawal of anti-metabolite and increase of corticosteroid dose. AKI occurred in almost half of patients and mortality in hospitalized patients reached 20%, reflecting greater disease severity than the general population.